Misc 7 - Prove tan-1 63/16 = sin-1 5/13 + cos-1 3/5 - Changing of trignometric variables and then applying formula

  1. Chapter 2 Class 12 Inverse Trigonometric Functions
  2. Serial order wise
Ask Download

Transcript

Misc 7 (Method 1) Prove tan-1 63/16 = sin-1 5/13 + cos-1 3/5 Let a = sin-1 5/13 , b = cos-1 3/5 Let a = sin-1 5/13 sin a = 5/13 We know that cos2 a = 1 sin2 a cos a = (1 sin2 ) = ("1 " 25/169) = ((169 25)/169) = (144/169) = 12/13 Let b = cos-1 3/5 cos b = 3/5 We know that sin2 b = 1 cos2 b sin b = ("1 cos2 b" ) = ("1 " (3/5)"2" )= ("1 " 9/25) = ((25 9)/25) = (16/25) = 4/5 Now we know that tan (a + b) = + /(1 ) Putting tan a = 5/12 and tan b = 4/3 tan (a + b) = (5/12 + 4/3)/(1 5/12 4/3) = ((5 3 + 4 12)/36)/(1 20/36) = ((15 + 48)/36)/((36 20)/36) = (63/36)/(16/36) = 63/36 36/16 = 63/16 Hence, tan (a + b) = 63/16 a + b = tan-1 (63/16) Putting values of a & b sin-1 5/13 + cos-1 3/5 = tan-1 (63/16) Hence L.H.S = R.H.S Hence Proved

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 8 years. He provides courses for Maths and Science at Teachoo. You can check his NCERT Solutions from Class 6 to 12.